A comprehensive review on mechanical, electromagnetic radiation shielding, and thermal conductivity of fibers/inorganic fillers reinforced hybrid polymer composites. Issue 10 (14th July 2020) - Hemath, Mohit; Mavinkere Rangappa, Sanjay; Kushvaha, Vinod; Dhakal, Hom Nath; Siengchin, Suchart
Abstract: Peripheral such as aerospace, armor, sensors, heat exchanger, automobile, storage, and any other electronic equipment are frequently subjected to varying mechanical and thermal stress, which substantially influence their reliability, life cycle, and performance. The aerospace sector, for example, is in constant research for the decrement in mass to achieve higher fuel efficiency through light weighting approach. It is due to the specific parameters that advanced polymer composites exhibit, there are growing research interests in heat management schemes, where both higher thermal characteristics and strength with significantly lower density are simultaneously essential. In the same manner, nanohybrid particles are commonly utilized as reinforcement fillers to enhance mechanical, electromagnetic shielding efficiency, and thermal characteristics of any polymer matrices. This survey discusses the polymer‐based nanocomposites incorporated with hybrid nanoparticles for applications in high‐performance materials. The subsequent interaction between the selected polymer matrix and hybrid nanofillers, which affects the characteristics of the polymer‐based nanocomposites: mechanical, electromagnetic radiation shielding efficiency as well as thermal conductivity have been critically reviewed. The hybrid nanoparticles' synergy facilitates effective dispersion without damaging the structures of the nanofillers tend to optimized electrical properties, thermal conductivity, and higher overall functionality of the fabricated nanocomposites.